Fostering Secondary School Students' Critical Thinking Skills through Social Studies Learning by Group Investigation Model - El Rizaq, Agung Dwi Bahtiar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This disruption era needs every student mastering critical thinking skills as the basis to maintain the competence. The central point that can be done to grow these skills is through education. This study aims to test the improvement of students' critical thinking skills through social sciences learning by Group Investigation model in VIII class containing 20 students. This study uses the Kemmis and McTaggart model of Classroom Action Research. The research instrument was in the form of observation sheets and tests which were analyzed using a comparative descriptive approach. The results of the study indicate that social studies learning by Group Investigation model can improve students' critical thinking skills, with the following implications; (1) The condition of critical thinking skills of pre-cycle students by 40% are in the less condition, and 35% are in the sufficient category; (2) In the first cycle, the students' critical thinking skills below the minimum standard have been reduced to 25%; (3) Then, only 15% of students have critical thinking skills below the minimum standard. This study recommends to another researcher try to find out another learning methods and models to improve students' critical thinking skills.